Effect of Marble Dust and Banana Fiber on Strength Characteristics of Pavement Quality Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
This study shows developing pavement  quality concrete mixtures incorporating marble dust as  partial replacement of cement as well as banana fiber.  There is a growing interest in the construction of concrete  pavements due to its high strength, durability, and better  serviceability and overall economy in the long run. This  study also shows that in view of the high flexural strength,  high values of compressive strength and high values of  split tensile strength, higher load carrying capacity and  higher life expectancy, the combination of 10 to 15%  marble dust replacement along with addition of 0.5 banana  fiber is ideal for design of Pavement Quality Concrete  (PQC). By replacing cement with marble dust and adding  fibers it has been possible to achieve savings in cement. To  produce thinner and green pavement sections of better  quality, which can carry the heavy loads, is nowadays  thrust.
Keywords: Pavement quality concrete (PQC); High strength concrete; Aggregates; Banana Fibre; Marble Dust.